Cancer immunotherapy in veterinary medicine: Current options and new developments. (January 2016) - Regan, Daniel; Guth, Amanda; Coy, Jonathan; Dow, Steven
Highlights: Developments in tumor immunotherapy are advancing rapidly. Autologous tumor vaccines are showing significant promise. Antibody targeted therapeutics will soon be a reality for cancer therapy in veterinary medicine. Checkpoint molecule targeted therapeutics show remarkable effects. Engineered T cells are the next generation of tumor immunotherapeutics. Abstract: Excitement in the field of tumor immunotherapy is being driven by several remarkable breakthroughs in recent years. This review will cover recent advances in cancer immunotherapy, including the use of T cell checkpoint inhibitors, engineered T cells, cancer vaccines, and anti-B cell and T cell antibodies. Inhibition of T cell checkpoint molecules such as PD-1 and CTLA-4 using monoclonal antibodies has achieved notable success against advanced tumors in humans, including melanoma, renal cell carcinoma, and non-small cell lung cancer. Therapy with engineered T cells has also demonstrated remarkable tumor control and regression in human trials. Autologous cancer vaccines have recently demonstrated impressive prolongation of disease-free intervals and survival times in dogs with lymphoma. In addition, caninized monoclonal antibodies targeting CD20 and CD52 just recently received either full (CD20) or conditional (CD52) licensing by the United States Department of Agriculture for clinical use in the treatment of canine B-cell and T-cell lymphomas, respectively. Thus, immunotherapy for cancer is rapidly moving to the forefront of cancer treatment options in veterinary medicine as well as human medicine.